Genomic data from African penguin ( Spheniscus demersus ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The African penguin (also known as jackass penguin and black-footed penguin) is endemic to southern African coasts. The pink gland above the eyes helps to adjust to changing temperatures: when it's hotter, more blood is sent to these glands to be cooled by the surrounding air. It is a charismatic species and is popular with tourists. The African penguin has declined rapidly and the International Union for Conservation of Nature (IUCN) classifies it as endangered. We sequenced the genome of an adult African penguin from Luderitz, Namibia (provided by Kim Labuschagne) to a depth of approximately 115x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.23Gb, with the contig and scaffold N50 values of 99.03Kb and 14.67Mb respectively. We identified 16134 protein-coding genes. ...